Analysis of Safety and Health of Radiation Officer at Pilot Plant BNCT - Yuliana Dian N; Soeparmi Soeparmi; Yohannes Sardjono (Fakultas Sains dan Matematika Universitas Kristen Satya Wacana, 2017)
Radiation is emission energy which derived from the process of transformation of atoms or nuclei unstable. The emission energy was emitted by a hoarse radiation, can cause changes in physical, chemical and biological material in its path so that the radiation worker should give special attention to health and safety during operate the installation using radiation. Limits opportunities for stochastic effects occur, or the risk resulting from the use of radiation that can be accepted by the public, and workers and prevent the occurrence of deterministic result of radiation harm to the individual. Equivalent dose of radiation received by workers or the public should not be beyond Dose Limit Value (NBD). This also applies to the radiation workers who operate tools for cancer therapy method using boron or Boron Neutron Capture Therapy (BNCT). BNCT is a method of new cancer therapies that are being developed, which combines methods of chemotherapy and radiotherapy. BNCT method utilizing 10B or boron compounds are likely to capture neutrons in thermal energy, which is produced by high - Linear Energy Transfer (LET). Medical examinations for radiation workers should be done regularly and follow the general principles of treatment work, namely the examination before work and after work. Threshold limit radiation exposure was 0.2 to 0.5 Sv. When a person is exposed to radiation overdose, the investigation dosage needs to be done specifically include biological dosimetry.